Construction and structure of the semidomes of the fiddler crab Minuca rapax (Brachyura: Ocypodidae) in southern Brazil - Carvalho, Renan D. [UNESP]; Pardo, Juan C.F. [UNESP]; Costa, Tânia M. [UNESP] (Oxford University Press (OUP), 2018)
Fiddler crabs construct and maintain above-ground sedimentary structures that vary in shape and function. We describe for the first time the behavior of the construction of semidomes, a type of sedimentary structure, in Minuca rapax (Smith, 1870) and the relationship of semidomes to other fiddler crab structures. We observed how semidomes are built and explored the relationship between the builders and semidome traits. Males use their first three ambulatory legs to pick up sediment from the surface and deposit sand at the edge of the opening to their burrows, shaping the semidome with their legs, carapace, and large claw. We found a positive relationship between the carapace width (CW) of the resident crab and two semidome measurements: structure width and burrow diameter, but there was no relationship between resident crab CW and semidome height.
Keywords: animal architecture; extended phenotype; hoods; sedimentary structures